Analisis Manajemen Strategi PT. TEMPO INTI MEDIA Tbk, dengan Pendekatan SWOT, SPACE, BCG, IE Matrix, dan Grand Strategy Matrix - I Made Santiasa (Konsorsium Dosen Institut Agama Islam Al-Yasini Pasuruan, 2026)
This study aims to analyze the business strategy of PT Tempo Inti Media Tbk in responding to digital disruption and changes in public information consumption patterns. The media industry has undergone a significant shift from print-based to digital platforms, requiring companies to transform in order to maintain sustainability and competitiveness. This research employs a descriptive qualitative approach using strategic management tools such as PESTEL analysis, Five Forces, IFE, EFE, SWOT, and QSPM to evaluate the company’s internal and external environments. The findings reveal that the company’s main strengths lie in its strong brand credibility, high-quality investigative journalism, and business diversification into digital media, data services, and training. Nevertheless, the company faces challenges including declining print revenues, the dominance of global digital platforms, and changing preferences of younger audiences toward fast and visual content. The recommended strategy is to accelerate digital transformation, strengthen subscription-based business models, and develop multimedia and data-driven innovations as new revenue streams. Through these strategies, the company is expected to sustain its competitive advantage and adapt continuously within the evolving digital media ecosystem.